2022
DOI: 10.3390/cancers14194586
|View full text |Cite
|
Sign up to set email alerts
|

Employment among Childhood Cancer Survivors: A Systematic Review and Meta-Analysis

Abstract: To date, there are heterogeneous studies related to childhood cancer survivors’ (CCS) employment rates. Given the importance of this topic, we aimed to perform a systematic review and meta-analysis to investigate the prevalence of employment among CCS and to examine its association with socio-demographic and clinical factors. We followed the PRISMA guidelines to search for pertinent articles in relevant electronic databases. Eighty-nine articles comprising 93 cohorts were included. The overall prevalence of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 123 publications
1
19
0
Order By: Relevance
“…In the area of employment, a recent systematic review and meta‐analysis focusing on employment status among CCSs revealed that approximately two‐thirds of these individuals were gainfully employed worldwide. This employment rate, however, is strongly influenced by socio‐demographic factors, emphasizing the need for comprehensive, multidisciplinary support and interventions 10 . In the present research, we first aimed to clarify the current status of CCSs in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the area of employment, a recent systematic review and meta‐analysis focusing on employment status among CCSs revealed that approximately two‐thirds of these individuals were gainfully employed worldwide. This employment rate, however, is strongly influenced by socio‐demographic factors, emphasizing the need for comprehensive, multidisciplinary support and interventions 10 . In the present research, we first aimed to clarify the current status of CCSs in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…This employment rate, however, is strongly influenced by socio-demographic factors, emphasizing the need for comprehensive, multidisciplinary support and interventions. 10 In the present research, we first aimed to clarify the current status of CCSs in Japan. For this purpose, we examined how interventions from the medical, educational, and administrative institutions affected the QOL of pediatric patients or adult CCSs in our institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 66% of all childhood cancer survivors are employed. A recent meta-analysis shows the lowest rate of employment for central nervous system tumor survivors, patients treated with cranial-radiotherapy and hematopoietic stem-cell transplantation (with employment rates of 51%, 53% and 56%, respectively) [ 12 ]. Thereby, late sequelae cognitive and motor impairments secondary to their primary disease, the time of its onset, treatment and adjuvant therapy significantly affect the whole life of cancer survivors.…”
Section: Introductionmentioning
confidence: 99%